ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL PADA KINERJA KARYAWAN DENGAN INTERNAL CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING - Rini Handayani; Aris Dwi Saputro (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
Human Resources is one of the resources that determine the success of an organization. Proper management of human resources can create a strong managerial system to support the productivity and success of the company. Therefore, it is necessary to have factors that can form quality human resources. This article aims to explore employee performance which is influenced by transformational leadership and internal CSR. Internal CSR also has a role as an intervening variable between transformational leadership and employee performance. The research model is multivariate and the analysis will use SMARTPLS. The research was conducted at the Public Works and Spatial Planning Office of Grobogan Regency with 110 employees who participated in this study. The sampling method used accidental sampling. The results show that transformational leadership and internal CSR can affect employee performance. Internal CSR can act as a mediation between transformational leadership and employee performance.